(3CSGSjGJ GdJfXje hGdGOGQIs - (3YHO GdSdGe(B, (3CHh bMas ((3GdGScfOQjI(B:s (3OGQ GdeYQaI GdLGeYjI(B,s, 2001)
(3GdJNWjW, GdJfXje, GdJhLjg, GdQbGHI hJbjje GdGOGA, GOGQI GdGYeGd GdOhdjI, fXe GdeYdheGJs
Keywords: (3GdGOGQI, GdJNWjWs; (3GdQbGHI, fXe GdeYdheGJs